Cyclostationary approach to detect flow-induced effects on vibration signals from centrifugal pumps. (1st January 2019) - Li, Shiyang; Chu, Ning; Yan, Peng; Wu, Dazhuan; Antoni, Jérôme
Highlights: Flow-induced effects of a centrifugal pump with splitter blades are studied. A pump vibration model is established as an amplitude-modulated model. Cyclostationarity is adopted to process the vibration signals from pumps. CFD simulations are conducted to obtain the flow-induced effects. The mechanism of flow-induced effects on vibration signals is elaborated. Abstract: This study aims to investigate the mechanism of flow-induced effects on vibration signals from centrifugal pumps by combining computational fluid dynamics (CFD) and signal cyclostationarity. A pump vibration model is established as an amplitude-modulated (AM) model, and the modulation mechanism is elaborated in detail. A general AM model is mathematically analyzed with spectral correlation density and spectral coherence, and analytic solutions of modulation intensity are derived. Transient CFD simulations under design and off-design conditions are conducted to obtain the pressure pulsation in the volute and the radial fluid forces on the impeller. Then, vibration signals from the pump and motor feet with two acceleration transducers are processed by spectral coherence. The signature of second-order cyclostationarity is detected at the shaft rotating frequency and blade passing frequency (BPF). The mean spectral coherence is used to evaluate the intensity of the modulating signals produced by the flow-induced effects. Finally, the signal processing results are compared with the unsteady CFD results under design and off-design conditions. These comparisons show a good agreement. Therefore, this study confirms that the flow-induced signals calculated by CFD can be considered as modulating components for pump vibration signals. The results provide solid supporting theory for designing low vibration pumps.